FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PERAWAT TERHADAP PENERAPAN SURGICAL PATIENT SAFETY FASE TIME OUT DI INSTALASI BEDAH SENTRAL - Ernawati, Yeni (MEDICA MAJAPAHIT, 2020)
Patient safety is a system where hospitals make patient care safer. The study aimed to determine the Factors Affecting Nurse’s compliance with the Application of Surgical Patient Safety Phase Time Out in the Central Surgical Installation of RSUD Moh Shaleh Hospital in Probolinggo. The type of research used correlational analytic research. The samples in this study were 30 nurses in the Central Surgical RSUD Moh Shaleh Hospital in Probolinggo that selected by total sampling. Data retrieval was done by using questionnaire sheets and Checklist. The results showed that 19 nurses (63.3%) had high motivation. Through the Chi Square test resulted p = 0,000 where p <0.05 so Ho was rejected which means a factor the most dominant one was Nurse Motivation (C=0,607). Training and regular assessment of the use of a checklist can be recommended to maintain a positive attitude among operating room staff regarding the importance of this kind of safety device in improving patient safety.